Néolibéralisme et Décentralisation dans les Etats Fédéraux - Andrew Ives (Nuevo mundo - Mundos Nuevos, 2008)
This paper attempts to fix the parameters of the the debate over decentralisation in France through a study of the situation in the federal States of Canada and the United States of America. After having established the perpetual nature of this debate in North America, we identify what distinguishes the contemporary debate from those in the past. Decentralisation has traditionally been defended by those on the left as a means to enhance the sense of belonging for citizens and as a step on the path towards the creation of new forms of participatory democracy. This leads us to bring to light the strange alliance that has been created on this issue between this left-wing tradition and a right-wing neoliberal political current that sees in decentralisation a way to reduce the presence of the State in the economy. We focus on this paradox and attempt to explain, both from a strategic and a theoretical point of view, why neoliberals have taken hold of the decentralisation issue. This analysis of the decentralisation debate in North America provides lessons for other countries tempted by a similar project, and clarifies some of the issues at stake